ผลของการใช้น้ำมันผสมระหว่างน้ำมันถั่วเหลืองกับปาล์มโอเลอินที่มีต่อการเกิดสารประกอบมีขั้วระหว่างกระบวนการทอดมันฝรั่งแท่งแบบน้ำมันท่วม - วิภาวรรณ กาฬสุวรรณ (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
The purpose of this study was to investigate the effect of soybean and palm olein oil blends on formation of polar compounds during deep-fat frying of french fries. From the studies of chemical and physical properties of soybean oil, palm olein oil, and the blends of these oils before frying (soybean oil, the blends of soybean and palm olein oil at the proportion of 70:30, 60:40, 50:50, 40:60, 30:70 (w/w), and palm olein oil ), the results showed that all oils had differences in fatty acid composition, viscosity, and color values. The measured values of polar compound, free fatty acid, and peroxide of those oils in all formulas were within The Food and Drug Administration standard limits. The results from the study of the effect of the proportion of oil in the formula, by frying 300 g of french fries at 180ํC for 6 minutes per batch and continuous frying each batch untill the frying time reached 12 hours, demonstrated that oil formula had significant effect on the formation of polar compounds (p[is less than or equal to]0.05). Moreover, the soybean and palm olein oil blend in the proportion of 30:70 (w/w) showed the lowest polar compound formation and the rate of changes of this formula on free fatty acid, peroxide value, viscosity, and color were lower than those of the other formulas. Therefore, this soybean and palm olein oil blend was chosen to study in the next step. By varying the frying condition of temperature and time for 160, 180, 200ํC and 6, 8, and 10 minutes, respectively, the results showed that frying condition had significant effect on the formation of polar compounds, free fatty acid, peroxide, viscosity, and color values (p[is less than or equal to]0.05). With the increasing of frying temperature and frying time, the polar compounds increased. The results from sensory evalutions by using quantitative descriptive analysis demonstrated that frying condition had significant differences on color, rancid, and hardness of french fries (p[is less than or equal to]0.05). The preference test results by using 9-point hedonic scale indicated that french fries, which were fried at 180ํC for 6 minutes per batch, gave the highest score on color, rancid, hardness, and overall acceptance (p[is less than or equal to]0.05). The regression analysis was used to predict the frying time untill 25% polar compounds in each formula were reached, it was found that soybean oil blended with palm oil at the proportion of 30:70 (w/w) for deep-fat frying french fries at the 180ํC for 6 minutes per batch could be fried continuously for 6.81 hours.